The role of trust in HPV vaccine uptake among racial and ethnic minorities in the United States: a narrative review - Nicole Harrington; Yuku Chen; Alana M O'Reilly; Carolyn Y Fang (AIMS Press, 2021)
Despite the clinically proven benefits of the human papillomavirus (HPV) vaccine in preventing cervical and other HPV-associated cancers, vaccination coverage has been suboptimal among adolescents and young adults in the United States (US), particularly among racial and ethnic minority adolescents. Historical legacies, combined with current racial/ethnic disparities in healthcare, may contribute to suboptimal uptake and completion of the HPV vaccine in part through differing levels of trust in doctors and healthcare institutions. The purpose of this narrative review was to characterize trust and its role in decision making about HPV vaccine uptake among US racial and ethnic minorities. We conducted a literature search using the PubMed database, and our search terms yielded 1176 articles. We reviewed 41 full-text articles for eligibility and included 20 articles in this review. These studies used varied measures of trust or mistrust and assessed trust in not only doctors/healthcare providers, but also other sources including pharmaceutical companies, media, and clergy. Our review findings revealed generally high levels of trust in doctors and healthcare providers, but less so in pharmaceutical companies. Mistrust of either healthcare providers, government agencies or pharmaceutical companies was consistently associated with less favorable attitudes and lower vaccine uptake. The downstream effects of mistrust may occur through selected health beliefs regarding the perceived efficacy and safety of the vaccine. Minority groups were more likely to report trust in family members, religious organizations, and media sources compared to their white counterparts. Decision making about vaccine uptake is a multilayered process that involves comparing the perceived benefits of the vaccine against its perceived risks. Understanding how trusted sources can effectively harness the tools of social and traditional media to increase knowledge and awareness may help combat misinformation about the HPV vaccine and improve engagement with diverse communities.